Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 1 - Section 1.8 - Simplifying Expressions - Exercise Set: 48

Answer

$\dfrac{1}{5}(9y+2)+\dfrac{1}{10}(2y-1)=2y+\dfrac{3}{10}$

Work Step by Step

$\dfrac{1}{5}(9y+2)+\dfrac{1}{10}(2y-1)$ Multiply the fractions by every term inside its respective parentheses: $\dfrac{1}{5}(9y+2)+\dfrac{1}{10}(2y-1)=\dfrac{9}{5}y+\dfrac{2}{5}+\dfrac{2}{10}y-\dfrac{1}{10}=...$ $...=\dfrac{9}{5}y+\dfrac{2}{5}+\dfrac{1}{5}y-\dfrac{1}{10}=...$ Simplify like terms: $...=\dfrac{10}{5}y+\dfrac{20-5}{50}=2y+\dfrac{15}{50}=2y+\dfrac{3}{10}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.